2019
DOI: 10.1111/den.13326
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic papillary large balloon dilation without sphincterotomy for users of antithrombotic agents: A multicenter retrospective study

Abstract: Background and Aim With an aging population, an increasing number of individuals on antithrombotic agents are diagnosed with large bile duct stones. Studies have shown the effectiveness of endoscopic papillary large balloon dilation (EPLBD) for removal of large bile duct stones. EPLBD without endoscopic sphincterotomy (EST) may reduce the risk of procedure‐related bleeding, but the safety of this procedure for users of antithrombotic agents remains unclear. Methods In this multicenter retrospective study, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Although several studies have shown that endoscopic sphincterotomy plus balloon dilation was safe and effective for large CBDS removal, owing to the improvements of laser technology, more and more endoscopists preferred lithotripsy plus balloon dilation. [26][27][28] Peroral cholangioscopy-guided lithotripsy achieved a technical success rate of 80%-86% in a single procedure, and was signi cantly more likely indicated for stones ≤30 mm in size than for stones with >30 mm in size. 29,30 In the present study, no CBDS had a size of 30 mm, and the technical success rate was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown that endoscopic sphincterotomy plus balloon dilation was safe and effective for large CBDS removal, owing to the improvements of laser technology, more and more endoscopists preferred lithotripsy plus balloon dilation. [26][27][28] Peroral cholangioscopy-guided lithotripsy achieved a technical success rate of 80%-86% in a single procedure, and was signi cantly more likely indicated for stones ≤30 mm in size than for stones with >30 mm in size. 29,30 In the present study, no CBDS had a size of 30 mm, and the technical success rate was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…To update the evidence for the previous KSGE guidelines, we performed a literature search and identified eight retrospective and prospective cohort studies. 53,59,[73][74][75][76][77][78] Various low-risk endoscopic procedures, such as double-balloon enteroscopy, 73,78 diagnostic endoscopy, 53,75 endoscopic papillary large balloon dilatation, 76 or endoscopic biopsy, 59,77 were evaluated to determine whether warfarin could be continued or discontinued before the procedures. All included studies indicated that the overall rate of early or delayed hemorrhage did not differ between the warfarin interruption and non-interruption groups.…”
Section: Statementmentioning
confidence: 99%
“…However, balloon dilation is contraindicated in cases with distal biliary strictures, due to the increased risk of perforation[ 21 ], whereas EST increases the risk of bleeding in patients on antithrombotic agents[ 22 ]. A recently published systematic review and metanalysis including 13 randomized controlled trials conducted on 1990 patients[ 23 ] focused on the treatment of large CBD stones using the three techniques.…”
Section: Stepwise Approach For the Management Of Difficult Common Bile Duct Stonesmentioning
confidence: 99%